Association of Medicare Advantage Penetration With Per Capita Spending, Emergency Department Visits, and Readmission Rates Among Fee-for-Service Medicare Beneficiaries With High Comorbidity Burden. (December 2021) - Park, Sungchul; Langellier, Brent A.; Burke, Robert E.; Figueroa, Jose F.; Coe, Norma B.
Rapid growth of Medicare Advantage (MA) plans has the potential to change clinical practice for both MA and fee-for-service (FFS) beneficiaries, particularly for high-need, high-cost beneficiaries with multiple chronic conditions or a costly single condition. We assessed whether MA growth from 2010 to 2017 spilled over to county-level per capita spending, emergency department visits, and readmission rates among FFS beneficiaries, and how much this varied by the comorbidity burden of the beneficiary. We also examined whether the association between MA growth and per capita spending in FFS varied in beneficiaries with specific chronic conditions. MA growth was associated with decreased FFS spending and emergency department visits only among beneficiaries with six or more chronic conditions. MA growth was associated with decreased FFS spending among beneficiaries with 11 of the 20 chronic conditions. This suggests that MA growth may drive improvements in efficiency of health care delivery for high-need, high-cost beneficiaries.